Penerapan Kuis Berbasis Teknologi Dalam Pembelajaran Sebagai Bentuk Evaluasi Pembelajaran - Astiza, Ajeng Kurnia; Husniati, Husniati; Nurhaedah, Siti; Kaninta, Novianti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study is motivated by the researcher's discovery of students in class IIIB who like to take quizzes at the end of learning. Initially, this quiz was only done manually in mathematics subjects, where students would form a line and then be asked questions one by one. This quiz is done as a form of evaluation of the learning that the teacher has done. When teachers do Indonesian language learning, such quizzes are not suitable because Indonesian language material has different characteristics from mathematics. So, the purpose of this research is to create a quiz that can contain different characteristics of the material and integrate it with technology that has never been done before, so that learning is more interesting, impressive, and effective for students by using the Wordwall website. This research is a classroom action research (PTK) conducted in two cycles. Data collection instruments used observation and evaluation scores. The results showed that the Wordwall website can improve student learning outcomes in each cycle. In the pre-cycle stage without using the Wordwall web, the learning achievement was only 31%. Then in Cycle 1 after the application of the Wordwall Web there was a fairly high increase of 63% until Cycle 2 there was an increase of 94% in student learning outcomes as a form of evaluation. From these data, it can be seen that the use of Wordwall web is suitable for Indonesian language subjects that have complex material characteristics and is proven to be able to improve students' learning outcomes and have an impact on students' activeness in learning.